Concise theology - Packer, J. I. (James Innell) (Wheaton, Illinois : Crossway, 2020)
"This book sets out in short compass what renowned theologian J. I. Packer perceives to be the permanent essentials of Christianity, viewed as both a belief system and a way of life. Packer concisely treats topics that run the gamut from knowing God as he has revealed himself in Scripture and nature to recognizing our desperate state in sin; from celebrating the joy of redemption in Christ to living in obedience, grateful for the Holy Spirit's enabling grace; from ordering our lives, families, churches, and governments in this sphere to anticipating the hope of eternal life and joy in God's presence. In this book Packer seeks to present theology with an eye toward both doxology and devotion-that is, the praise of God and the practice of godliness"--
Originally published: Wheaton, Ill. : Tyndale House, c1993.
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal -- Popular works